Identification of New Putative MicroRNAs in Epstein-barr Virus Genome for Medical and Biotechnological Applications - Danaeifar, Mohsen (Archives of Advances in Biosciences, 2024)
Introduction: MicroRNAs play important roles in regulating gene expression in animals and plants. Many studies used these genetic elements to up- or down-regulate human gene expression. It has been shown that viral miRNAs can target and regulate not only viral genes but also host genes. To date, 48 miRNAs have been identified in Epstein-Barr virus (human gamma-herpesvirus 4). This virus can invade and reside in many human tissues such as epithelial or immune system cells. In this study, we evaluated a novel method of finding miRNAs in the Epstein-Barr virus (EBV). Materials and Methods: The entire genome content of human gamma-herpesvirus 4 (EBV) was searched using ab initio prediction algorithm by miRNAFold. Selected sequences screened by homology algorithm of miRBase web server. Results: Among the identified 12 sequences, two putative miRNAs were selected and their properties were further investigated. The main human gene target of the putative miRNA-1 was BCL11A gene that is related to the B-cell lymphoma, and that of putative miRNA-2 was ZBTB18 gene which is mainly related to the mental retardation. Previous studies used known EBV miRNAs incorporated in delivering vectors such as lentiviral vectors to target various human genes. The introduced two miRNAs can target genes in some malignancies and other types of disorders. Conclusion: Because of the high stability of the proposed putative miRNAs, they can be used experimentally to regulate human genes.